Nonlinear optical studies of phthalocyanines and their conjugates with nanomaterials - Sanusi, Sikiru Olukayode (Rhodes University, Faculty of Science, Department of Chemistry, 2015)
A number of metallophthalocyanines (MPcs) and metal-free phthalocyanines (Hâ‚‚Pcs) have been synthesized and characterized using various characterization tools such as Â¹H-NMR, TOF mass spectrometry, FT-IR, UV-visible spectrophotometry and CHNS elemental analysis. Some of the MPcs were covalently linked to nanomaterials such as silica nanoparticles (SiNPs), single-walled carbon nanotubes (SWCNTs), magnetite nanoparticles (MNPs) and quantum dots (QDs), or embedded in polymer thin-films using poly(methyl methacrylate) (PMMA) and poly(acrylic acid) (PAA) as the polymer sources. The phthalocyanine-nanomaterial composites (Pc-NMCs) were characterized with FT-IR, UV-visible spectrophotometry, transmission electron microscopy (TEM), thermogravimetry analysis and X-ray diffractometry. The nonlinear optical (NLO) properties (using the open-aperture Z-scan technique) of the MPcs and the Pc-NMCs were investigated. In general, most of the investigated MPcs showed good optical limiting behaviors, except for a few, like the non-peripherally-substituted 2-pyridyloxy phthalocyanines, which showed inhibited NLO response as a result of the ring-strain effects. The absence of a metal center was found to greatly reduce the inherent high nonlinearities expected of some of the phthalocyanine complexes. The octaphenoxy derivatives (61a "“ 61e) were found to exhibit reverse saturable absorption (RSA) that depends on the singlet-singlet transitions, hence making them less reliable optical limiters. The optical limiting properties of the MPcs were improved in the presence of nanomaterials such as the QDs, MNPs and SWCNTs, with MPc-QDs showing the best optical limiting behavior of the three. SiNPs have no significant effect on the optical limiting behavior of the MPcs. The optical limiting properties of the MPcs were greatly enhanced in the presence of PMMA or PAA polymers. The PAA polymer showed better optical limiting behavior compared to PMMA
Keywords: Phthalocyanines; Nonlinear optics